THE INFLUENCE OF TAX KNOWLEDGE, E-FILING, AND TAX SANCTIONS ON INDIVIDUAL TAXPAYER COMPLIANCE: A CASE STUDY AT PT BENUA JAM INTERNUSA - yuana; Lin Oktris (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2025)
This study aims to analyze the effect of taxation knowledge, the application of e-filing, and tax sanctions on individual taxpayer compliance. This study was conducted on employees of PT Benua Jam Internusa with a total of 157 individuals. A simple random sampling technique was used in sampling, resulting in 61 respondents being selected, with 58 respondents who filled out the questionnaire completely. Data collection was conducted through a survey using a structured questionnaire, and data analysis was performed using the Partial Least Squares (PLS) method. The results showed that tax knowledge has a positive and significant effect on individual taxpayer compliance. Similarly, the application of e-filing and the effective enforcement of tax sanctions can increase the level of compliance. These findings indicate that increasing tax awareness, developing digital infrastructure, and optimizing law enforcement mechanisms can significantly encourage tax compliance. Therefore, this study recommends that tax authorities strengthen public socialization, especially through social media platforms, to increase taxpayers' understanding and involvement in fulfilling their tax obligations.